Type 2 Inflammatory Responses in Autoimmune Demyelination of the Central Nervous System: Recent Advances - Massimo Costanza (Journal of Immunology Research)
Type 2 immunity has long been confined to a restricted spectrum of responses, mostly including allergic reactions to innocuous environmental triggers. However, growing evidence suggests that cells and mediators typically associated with type 2 inflammation are involved in several physiopathological conditions, such as defense against toxic substances, anticancer immunity, and autoimmune diseases. In neuromyelitis optica, an autoimmune demyelinating disorder of the spinal cord and optic nerve, eosinophils extensively infiltrate lesions in the central nervous system (CNS) and promote tissue pathology in experimental models of this disease. Next-generation sequencing of CD4+ T cells isolated from a specific subtype of multiple sclerosis plaque has uncovered an unexpectedly Th2 profile of these cells. Even mast cells and other allergic mediators have been implicated in the modulation and/or effector mechanisms of autoimmune reactions against the CNS. In this review article, the most recent developments showing the involvement of type 2 inflammatory components in CNS autoimmunity are summarised and possible lines of further investigation are discussed.